2001
DOI: 10.2134/agronj2001.932271x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Soils to Achieve Greater Water Use Efficiency

Abstract: Y/T ϭ m/T max [2] Water use efficiency (WUE) represents a given level of biomasswhere Y is the total dry matter production, T is the or grain yield per unit of water used by the crop. With increasing transpiration, m is a coefficient, and T max is the daily concern about the availability of water resources in both irrigated free water evaporation. Water use efficiency is estiand rainfed agriculture, there is renewed interest in trying to develop mated using the total water use (ET) from a crop suran understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
306
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 506 publications
(334 citation statements)
references
References 67 publications
18
306
0
10
Order By: Relevance
“…Similarly, Davies et al (2011) showed how, by applying mulches, it could affect more directly WUEc as they can modify soil reserves, minimizing soil evaporative losses and consequently improving water soil infiltration. These results are in agreement with some reviews showing how surface residue management or mulching can improve WUEc by reducing soil evaporation and runoff in other crops (Davies et al 2011;Hatfield et al 2001).…”
Section: Mulchingsupporting
confidence: 92%
“…Similarly, Davies et al (2011) showed how, by applying mulches, it could affect more directly WUEc as they can modify soil reserves, minimizing soil evaporative losses and consequently improving water soil infiltration. These results are in agreement with some reviews showing how surface residue management or mulching can improve WUEc by reducing soil evaporation and runoff in other crops (Davies et al 2011;Hatfield et al 2001).…”
Section: Mulchingsupporting
confidence: 92%
“…Spiders are sensitive to both microclimate and habitat structure, and mulch may provide suitable burrowing habitat for groundhunting spiders that need specific humidity and temperature conditions (Riechert and Bishop 1990, Uetz 1991, Bell et al 2001. Covering the surface of bare soil with mulch reduces soil water evaporation by decreasing soil temperature, preventing vapor diffusion, absorbing water vapor into the mulch, and reducing wind speed gradients at the soil-atmosphere level (Hatfield et al 2001). The negative correlation of Gnaphosidae activity density with concrete cover and bare soil may be related to the inefficiency of humidity and temperature regulation on these types of ground cover.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, increased tree height may provide more canopy cover to spiders. Canopy cover and mulch can provide temperature and humidity regulation for species-specific habitat requirements (Riechert and Bishop 1990, Hatfield et al 2001, Lin 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to these agricultural droughts is critical to increasing and maintaining crop productivity. Soil management practices such as modified tillage, crop residue management, and soil nutrient status have been shown to increase water use efficiency and are a key means of adaption to periods of water stress (Hatfield et al 2001). Nutrient additions increased water use efficiency up to 25 % and conferred significant resilience of yields during Bdrought^years (Sileshi et al 2008).…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%